Analisis Bibliometrik Penerapan Balanced Scorecard Dalam Pengukuran Kinerja Di Sektor Publik - Romi Ali Yuliansah; Dendi Pribadi Pratama (Jurnal Ilmiah Administrasita', 2025)
This study analyzes the application of the Balanced Scorecard (BSC) as a performance measurement tool in the Indonesian public sector through a bibliometric approach. BSC, with four main perspectives-financial, customer, internal business processes, and learning and growth-is expected to improve efficiency, accountability, and quality of public services. The research method used was bibliometric analysis with VOSviewer software to map inter-topic relationships in the literature related to BSC in the public sector. The results showed that BSC implementation in Indonesia still faces challenges, such as limited resources and infrastructure. This study provides recommendations for government agencies to implement BSC effectively, through training, technological support, and strong leadership. BSC implementation is expected to help public organizations achieve their strategic goals and increase public trust.